Investigating the Role of Explicit Instruction in SLA Motivation in Pakistani ESL Classroom (Journal of Asian Development Studies, 2025)
The research aims to investigate the role of explicit instruction in enhancing motivation in the Pakistani ESL classroom. In Second Language Acquisition (SLA), motivation plays a significant role, especially in the classroom. Explicit instruction is a great way to foster motivation in the ESL classroom. Gardener’s (1985) Socio-Economic Model of Motivation is used as a theoretical lens to investigate the relationship between explicit instruction and motivation in SLA. A sequential explanatory mixed-methods research design is used to examine. There are 100 participants in the research, and data are collected via a questionnaire. Descriptive data is further analysed statistically. The predictive ability of explicit instruction over motivation in learners is assessed through regression analysis. The findings reveal that explicit instruction positively predicted ESL learners’ motivation levels. A considerable amount of variance is highlighted by the regression model. The outcomes imply that motivation and confidence level are all increased by explicit instruction. The statistical results are correlated with descriptive findings. Moreover, the study highlights the pedagogical importance of explicit instruction, as it helps build motivation in the ESL classroom.